Fear of Missing Out dan Tiktok Dalam Membentuk Keputusan Pembelian Produk Skincare di Era Digital - Ratih Komala Dewi (Journal of Digital Business and Management, 2026)
Social media has fundamentally transformed consumer behavior in obtaining information and making purchasing decisions. TikTok has evolved into a social commerce platform capable of influencing consumer preferences through short-form videos, user-generated content, live shopping, and influencer marketing. Meanwhile, the phenomenon of Fear of Missing Out (FOMO) encourages individuals to follow digital trends, potentially influencing purchasing decisions, particularly in the skincare industry. This study aims to examine the influence of FOMO and TikTok on skincare purchase decisions in the digital era. A quantitative associative approach was employed involving 63 female students who use Daviena Skincare products. The respondents were selected using saturated sampling, and the data were analyzed using multiple linear regression with SPSS. The findings reveal that FOMO does not significantly affect purchase decisions, whereas TikTok has a positive and significant influence. Simultaneously, both variables significantly affect purchase decisions, explaining 45.5% of the variance. These findings indicate that the effectiveness of social media plays a more dominant role than psychological FOMO in shaping skincare purchase decisions. The study provides practical implications for businesses in developing more effective digital marketing strategies through social media.